PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF PADA MATA PELAJARAN IPA KELAS VII DI MTs NEGERI 2 PONTIANAK - Herlina Herlina; Ernawati Ernawati; Lydia Sintiani; Roby Afriyanto; Helmina Aprida (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to find out: (1) Development of Interactive Multimedia-Based Learning Media in Science Subjects Science object material and its teaching for Class VII MTs Negeri 2 Pontianak, (2) Feasibility of Interactive Multimedia-Based Learning Media Products in Science Subjects Science object material and its understanding Class VII of MTs Negeri 2 Pontianak, (3) Student Responses to Interactive Multimedia-Based Learning Media in Science Subjects Science object material and its memorandum for Class VII MTs Negeri 2 Pontianak. The method used in this research is R&D (Research and Development) research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The data analysis technique used is qualitative and quantitative data analysis. The data collection tools are questionnaires, documentation, and interviews. The subjects in the study consisted of media expert respondents, material experts, small-scale and large-scale trial respondents. The small-scale trial consisted of 10 students and the large-scale trial consisted of 35 students. The results of the media expert test obtained 92.5% in the